Relation of statin use prior to admission to severity and recovery among COVID-19 inpatients (2020)
The impact of statins, ACE inhibitors (ACEi) and angiotensin II receptor blockers (ARBs) on COVID-19 severity and recovery is important given their high prevalence of use among individuals at risk for severe COVID-19. We studied the association between use of statin/ACEi/ARB in the month before hospital admission, with risk of severe outcome, and with time to severe outcome or disease recovery, among patients hospitalized for COVID-19. We performed a retrospective single-center study of all patients hospitalized at UCSD Health between February 10-June 17, 2020 (n=170 hospitalized for COVID-19, n=5281 COVID-negative controls). Logistic regression and competing risks analyses were used to investigate progression to severe disease (death or intensive care unit admission), and time to discharge without severe disease. Severe disease occurred in 53% of COVID-positive inpatients. Median time from hospitalization to severe disease was 2 days; median time to recovery was 7 days. Statin use prior to admission was associated with reduced risk of severe COVID-19 (adjusted OR 0.29, 95% CI 0.11-0.71, p<0.01) and faster time to recovery among those without severe disease (adjusted HR for recovery 2.69, 95% CI 1.36-5.33, p<0.01). The association between statin use and severe disease was smaller in the COVID-negative cohort (p for interaction=0.07). There was potential evidence of faster time to recovery with ARB use (aHR 1.92, 95% CI 0.81-4.56). In conclusion, statin use during the 30 days prior to admission for COVID-19 was associated with a lower risk of developing severe COVID-19, and a faster time to recovery among patients without severe disease.